Deformation mechanism and control technology of gob-side roadway with continuous mining and continuous backfilling: a case study - Dingchao Chen; Xiangyu Wang; Jianbiao Bai; Feiteng Zhang (Geomatics, Natural Hazards & Risk)
Gob-side roadways are excavations created during the mining process, serving to alleviate mining-induced stress. Previous studies have predominantly focused on the caving method, neglecting the examination of failure mechanisms in gob-side roadway associated with continuous mining and continuous backfilling (CMCB). In this study, focusing on Sima Coal Mine, we employed numerical simulation method to thoroughly investigate the full-cycle stress evolution patterns of the gob-side roadway. The numerical simulation results reveal that during the upper working face mining period, severe stress concentration phenomena occur within the coal pillars, with peak stresses reaching 36.0 MPa. Throughout the mining period of next working face, as the CMCB process progressed, the coal inside the working face was gradually replaced by the filling body, forming various coal pillars with decreasing widths. The alternant load between the coal pillar and filling body led to the gradual increase of the internal stress of the coal pillar, with the peak stress reaching 45.0 MPa. To mitigate stress concentration in the surrounding rock of the roadways, this study proposes a control methodology that incorporates "directional control of hydraulic fracturing slots" in conjunction with "reinforcement support of coal pillars" and "temporary support of single hydraulic props" as core components. Industrial experiments were conducted to validate the efficacy of the proposed control techniques. Field monitoring results demonstrate significant improvements in the stress environment, effectively mitigating deformation of roadway.